Immunogenic Cross-Reactivity between Goose and Muscovy Duck Parvoviruses: Evaluation of Cross-Protection Provided by Mono- or Bivalent Vaccine - Vilmos Palya; Anna Zolnai; Balázs Felföldi (Vaccines, 2022)
To investigate the immunogenic cross reactivity between goose parvovirus (GPV) and Muscovy duck parvovirus (MDPV), cross-neutralization was carried out with serum samples collected from birds after infection with one of the two waterfowl parvoviruses. The significantly higher virus neutralization titer obtained against the homologous virus than against the heterologous one suggests important differences between the GPV and MDPV antigenic make up that affects the induced protective virus-neutralizing antibody specificity. This was further confirmed by cross-protection studies carried out in waterfowl parvovirus antibody-free Muscovy ducks immunized at one day of age with whole-virus inactivated oil-emulsion vaccines containing either GPV or MDPV as a monovalent vaccine, or both viruses as a bivalent vaccine. Protection against the clinical disease (growth retardation and feathering disorders) provided by the monovalent vaccine was complete against homologous virus challenge at 2 weeks post-vaccination, while the protection against the heterologous virus challenge was significantly lower (p < 0.001). Only the bivalent vaccine containing both goose and Muscovy duck parvoviruses in an inactivated form protected the birds (90–100%) against both waterfowl parvoviruses that can cause disease in Muscovy ducks. Both the cross-neutralization and cross-protection results indicated that adequate protection in Muscovy ducks against the two waterfowl parvoviruses could be achieved only with a vaccine containing both goose and Muscovy duck parvoviruses. Our results showed that the inactivated vaccine applied at one day of age could induce fast immunity (by 2 weeks post-vaccination), providing complete clinical protection in maternal antibody-free birds. It was also demonstrated that day-old vaccination of ducks with maternal antibodies with bivalent vaccine induced active immunity, resulting in 90 to 100% protection by 3 weeks of age, after the decline of maternal antibodies. A booster vaccination administered at 3 weeks of age following the day-old vaccination resulted in a strong and durable immunity against the clinical disease during the susceptible age of the birds.